Properties of worm casts under secondary tropical forest regrowth - Vleeschauwer, D. de; Lal, R. (1981)
We compared the physical and chemical properties of worm casts with the properties of the surface 0 to 10 centimeters of six soils along a toposequence developed on basement complex rocks in southwestern Nigeria. Casts contained less sand and more silt and clay than the surface soil. Bulk density and structural stability of worm casts were generally greater than the surface soil. The kinetic energy of falling raindrops required to disrupt casts was 5 to 54 times greater than that required to disrupt natural soil aggregates. Worm casts had lower pH, about two to six times more organic matter content, two to four times more nitrogen, two to eight times more Bray phosphorus, and two to six times more cation exchange capacity than the parent soil.